Odpowiedzi

2010-04-14T18:19:44+02:00
2010-04-14T18:27:46+02:00
A) 3[3(3x-4)-4]-7=-2[-2(-2x+5)+5]+5
3[(9x-12)-4]-7= -2[4x-10 +5]+5
3[9x-16]-7= -8x+10+5
27x-48-7=-8x+15
27x+8x=70
35x=70
x= 2

b) 4[4(4x+9)]-9 =6[6(6x-2)+2]-4(38x+1)
4[16x+36]-9=6[36x-12+2]-152-4
64x+144-9= 216x-60-156
64x+135=216x- 216
-152x=- 351
x= 2 47/152


c) -2(2x+4)+4(4x+8) =2(8x+4)-4(x-4)
-4x-8+16x+32= 16x+8-4x+16
12x+24= 12x+24
0=0
2010-04-14T18:30:19+02:00
A) 3[3(3x-4)-4]-7=-2[-2(-2x+5)+5]+5
3[9x-12-4]-7=-2[4x-10+5]+5
27x-36-12-7=-8x+20-10+5
27x+8x=20-10+5+36+12+7
35x=70/:35
x=2

b) 4[4(4x+9)-9] =6[6(6x-2)+2]-4(38x+1)
4[16x+36-9]=6[36x-12+12]-152x-4
64x+144-27=216x-72+72-152x-4
64x-216x+152x=-4-144+27
0=-121

c) -2(2x+4)+4(4x+8) =2(8x+4)-4(x-4)
-4x-8+16x+32=16x+8-4x+16
-4x+16x-16x+4x=8+16+8-16
0=16